Challenges of sex education for adolescents with autism spectrum disorder from the Saudi family’s perspective - Shakuri, Manar A.; Alzahrani, Hassan M. (Frontiers in Education, 2023)
The purpose of this research was to better understand the challenges, as well as ways to overcome the aforementioned challenges, associated with sex and reproductive health education for parents of adolescents with autism spectrum disorder (ASD) from the perspective of parents. A qualitative multiple case study approach, including interviews and document analysis, was conducted to answer the research questions. The participants included 9 parents of adolescents with ASD, including (4) fathers and (5) mothers. Their children’s ages ranged from (13–19) years. Inductive coding was conducted to analyze the data collected. The findings suggested several challenges exist, including parents’ lack of knowledge regarding sex and reproductive health education and training on how to effectively teach their children. This lack of knowledge may contribute to unacceptable social demonstrations of sexuality by individuals with ASD, which creates another challenge for parents. The findings related to the second research question indicated families of individuals with ASD need more awareness and education, particularly on how to effectively educate their children on sexual matters. The importance of education regarding sexual matters for individuals with ASD within the school and community was also realized. The findings could help the Ministry of Education establish educational programs to ensure schools are equipped to educate individuals with ASD on sexual matters. The programs could also be beneficial if they provided training to parents on how to effectively provide sexual education to their adolescent children. The findings of this research could additionally provide insight to parents, general education teachers, and special education teachers on the importance of sex and reproductive health education for children with ASD.